Rancang Bangun Sistem Informasi Pemantau Kesehatan Balita Menggunakan Sistem Inferensi Fuzzy - Mahar, Boy Jehezkiel Kamanang; Raharja, I Made Sunia; Putri, Gusti Agung Ayu (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 4 No 2 (2023): JITTER, Vol.4, No.2, August 2023., 2023)
Proper use of Information Technology in the health sector will significantly help the management of information become easier to done, business processes become more effective than before, and most importantly, services for the community can be done more efficiently, better and more accurately. The Indonesian government is eager to become an independent country, and of course, this can be achieved with the optimal next generation of the nation. However, the facts on the ground cause nutritional problems, and malnutrition occurs in Indonesia. Cases of hunger and poor nutrition are not monitored because the current medical record application has not been able to provide information on the nutritional status of children under five automatically. The impact is that many problems about malnutrition and malnutrition are not well monitored given the complete medical record data they have. This study aims to discuss and develop the Toddler Health Monitoring module, which is an additional component in the application of medical records. Fuzzy Tsukamoto's inference method is used to create a reasoning engine that can determine the nutritional health status of toddlers because this method is flexible and improves data on output, it is easier, can be accepted by many people, and it is more suitable to understand by the humans.